Essential hypertension onset in a 12-year-old adolescent - Shalihin, Mohd Shaiful Ehsan; Harun, Zulkifli; Osman, Iskandar Firzada (Penerbit Universiti Kebangsaan Malaysia, 2020)
Essential hypertension in adolescents is increasing in trend worldwide in view of increasing prevalence of childhood obesity and sedentary lifestyle. Generally, secondary hypertension is suspected if it occurs at pre-pubertal age or presented with resistant hypertension. We reported a case of 12-year-old adolescent male diagnosed with essential hypertension during opportunistic screening with suboptimal blood pressure control at primary care. Poor response of his blood pressure control despite his compliance to medications had cause him emotional distress. We referred this child for assessment of secondary hypertension but it turned out to be negative. Surprisingly, his blood pressure responded well with prazosin and diltiazem combination during adjustment period prior to renovascular assessment. His hypertension is well controlled till now. This case proved that essential hypertension is still possible in early non-morbid obese adolescent despite negative family history of hypertension. Individualised treatment should be adapted rather than questioning the compliance of the adolescent.